Contribution to the Miniaturization of Antennas: State of the Art - Tarbouch, Mohamed; Elamri, Abdelkebir; Terchoune, Hanae (Discoveries in Agriculture and Food Sciences, 2016)
Nowadays, communications systems have become more mobile and personal, that means materials used must be as smaller as possible. Low weight reduced volume and low cost are some of the characteristics that must be accomplished in modern telecommunication equipment. It is well known that the antenna is one of the most important devices in the radiofrequency (RF) section. This element needs to perform effectively according to the necessities. To achieve low weight, small volume and low cost, the size needs to be reduced, but keeping the main characteristics. The size reduction of antennas can be made by several techniques according to the type of the element. In this study we will present the fundamental limitations of small antennas as a major constraint of antenna miniaturization, then we will discuss major techniques that have been reported in literature to reduce the size of an antenna. Feasibility, features, effects on the miniaturisation of antennas of each technique will be presented and discussed. At the end of this study we will give some examples of real systems that used antennas miniaturization techniques.